2020
DOI: 10.1177/1099800420951984
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Cerebrovascular Disease is Associated With Severity and Mortality of COVID-19: A Systematic Review and Meta-Analysis

Abstract: At present, COVID-19 is raging all over the world. Many comorbidities, such as diabetes mellitus (OR = 2.67, 95% CI = 1.91–3.74) and hypertension (OR = 2.3, 95% CI = 1.76–3.00), have been shown to worsen the patient’s condition. However, whether cardio-cerebrovascular disease will affect COVID-19 remains unclear. In this meta-analysis, we collected studies from PubMed, Wed of Science and CNKI (Chinese) to July 25, which reported COVID-19 patients with and without cardio-cerebrovascular disease as well as their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In a similar way, we found that HCWs with chronic conditions were more prone to get vaccinated against COVID-19. This finding makes sense since HCWs with comorbidity is a high-risk group for complications and death from COVID-19 as this is the case for the general population also according to several meta-analyses [6670]. Older HCWs with comorbidity confront COVID-19 with fear and anxiety affecting critically their decision to accept a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 94%
“…In a similar way, we found that HCWs with chronic conditions were more prone to get vaccinated against COVID-19. This finding makes sense since HCWs with comorbidity is a high-risk group for complications and death from COVID-19 as this is the case for the general population also according to several meta-analyses [6670]. Older HCWs with comorbidity confront COVID-19 with fear and anxiety affecting critically their decision to accept a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 94%
“…Ten moderate quality systematic reviews examined associations between CVD and outcomes with COVID-19. 20 , 21 , 23 , 31 , 33 , 36 , 38 , 39 , 44 , 49 The largest of which (Luo et al .,) suggested CVD was associated with 2.65 times higher odds of mortality with COVID-19 [pooled odds ratio (OR) 2.65, 95% confidence interval (CI) 1.86–3.78, n = 30 studies, considerable heterogeneity (I 2 = 86%)]. 33 …”
Section: Resultsmentioning
confidence: 99%
“…This result has been based on considering 852 patients (603 survivors and 249 non-survivors) with confirmed SARS-CoV-2 infection from four retrospective Chinese studies. Several meta-analyses confirmed such association [ [139] , [140] , [141] ]. Particular precautions should be taken in the management of COVID-19 patients with preexisting cerebrovascular disease.…”
Section: Interrelation Between Covid-19 and Disorders With Mixed Or Mmentioning
confidence: 86%